2013
DOI: 10.1155/2013/367812
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Bismuth Sulfide Nanorods from Spherical-Shaped Amorphous Precursor Particles under Hydrothermal Condition

Abstract: A surfactant/solid-template-free hydrothermal process has been developed for the synthesis of single-crystalline nanorods of bismuth sulfide (Bi2S3) using triethanolamine as a complexing agent for the Bi3+ions and elemental sulfur, solubilized in monoethanolamine, as the sulfur source. X-ray diffraction and morphological studies of a series of samples synthesized at different reaction conditions suggest that the growth of nanorods occurred at the expense of the low-crystalline spherical precursor particles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…24,25 In order to understand the effect of electron dose on bismuth(III) 109 ethylxanthate, circular discs of 50 µm were patterned using an electron beam to perform micro-FTIR and micro-Raman spectroscopies [Figures 2(c Analysis of the same using micro-Raman spectroscopy [Figure 2(d)] shows the appearance of characteristic peaks of Bi2S3 at 232, 256, 307, and 428 cm -1 . [30][31][32] In other words, the organic parts in bismuth(III) ethylxanthate, i.e., the xanthate moieties, decompose under an electron beam leaving behind Bi2S3. Appearance of Bi2S3 makes the exposed resist insoluble in organic solvents such as iso-propyl alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 In order to understand the effect of electron dose on bismuth(III) 109 ethylxanthate, circular discs of 50 µm were patterned using an electron beam to perform micro-FTIR and micro-Raman spectroscopies [Figures 2(c Analysis of the same using micro-Raman spectroscopy [Figure 2(d)] shows the appearance of characteristic peaks of Bi2S3 at 232, 256, 307, and 428 cm -1 . [30][31][32] In other words, the organic parts in bismuth(III) ethylxanthate, i.e., the xanthate moieties, decompose under an electron beam leaving behind Bi2S3. Appearance of Bi2S3 makes the exposed resist insoluble in organic solvents such as iso-propyl alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…4b ) indicated no detectable signal from sulfur. However, after etching, the surface showed a broad peak approximately at 221.0 eV, which can be assigned to the binding energy of S 2− state in Bi 2 S 3 [ 30 ]. This result indicated that Bi-rich surfaces of Bi 2 S 3 quantum dots were produced, which is consistent with metal-chalcogenide nanocrystals synthesized in the presence of coordinating ligands bound covalently to cations [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Being a tetradentate ligand containing three -OH and a lone pair of electrons localized on the N atom, it forms a stable [Cu(TEA) n ] 2? complex with metal ions (n is the coordination number of metal ion) (Panigrahi and Pathak 2013). The formation of this complex ion is highly favorable in order to control the reaction (Liufu et al 2008).…”
Section: Raman Spectroscopic Studymentioning
confidence: 99%